Darwinism in the Second Half of the Nineteenth Century in Latin America - Velázquez Fernández, Héctor (My University, 2014)
The chapter explains about the Darwinism in the second half of the nineteenth century could be framed according to Thomas Glick's models. Glick suggests that the main attitudes of scientific communities or other social groups towards new ideas could be: a combination of anxiety and opposition, or a combination of acceptance and adaptation. It is important to mention from the outset, that the circumstances of the reception of Darwinism in Peru reflect the Latin American environment in the second half of the nineteenth century: a lack of resources, a small scientific community and a low esteem in scientific fields. Since no detailed studies in favour of or against Darwinism appeared before the twentieth century, press articles were the space for the discussion of Darwinism in Mexico during the late nineteenth century. Thus the chapter briefly explains and analyses the characteristic features of the Darwinism in several South American countries, ending with a short reflection on the attitudes towards Darwinism. © Routledge
Keywords: Religion and science; Latin America